Experimental and Numerical Modal Analysis of the Carbon Composite Plate Damaged by Cut - Vavro, Jan; Vavro, Jan; Vavrova, Alena (Manufacturing Technology Journal, 2019)
The given paper is closely connected with the experimental and numerical modal analysis of the carbon composite plate damaged by cut. In relation to the tested carbon composite, modal analysis was performed by help of special measuring device Pulse 12. The mentioned device was supplied by company Bruel & Kjear and the experimental measurements were carried out using damaged and undamaged plate sample which were prepared from the mentioned material hereinbefore. The investigated and analyzed plates of carbon composite were made of six layers of carbon fibres and they were arranged under the angle 90º (it is like fabric material made off carbon fibres). The layers arranged in the given way were joined by epoxide resin MGS 285. The experimental measurement of eigenfrequencies of carbon composite plates was carried out using the undamaged and damaged sample with proportions 78 mm x 78 mm while ten measurements were performed for each one specified site of the sample. In relation to the damaged plate sample, there was cut in length of 20 mm in the centre border. The finite element method in the software system ADINA v.8.6.2 was used for numerical analysis of the eigenfrequencies.
Keywords: modal analysis; eigenfrequencies; carbon composite; finite element method